Спонтанна флора національного ботанічного саду імені М.М. Гришка НАН України (м. Київ). Повідомлення 3. Адвентивні види: ергазіофіти - Shynder, O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2019)
Objective – to study the species composition and structure of spontaneous flora in M.M. Gryshko National Botanical Garden of the NAS of Ukraine (Kyiv). Material and methods. The study was conducted in 2010–2018 on the territory of the Botanical Garden. We conducted an inventory of escaped plants according to generally accepted methods using our own developed selection criteria. Results. The list of escaped plants of the spontaneous flora of the National Botanical Garden includes 143 taxa, which is 22.0 % of the total flora. More than 10 escaped plants are discovered outside the Botanical Garden in the adjoining areas of the city zone. An example of a successful expansion beyond the Botanical Garden is Corydalis caucasica. Among escaped plants there are both invasive plants (these species constitute the majority) and rare plants. Conclusions. The total number of escaped plants in the National Botanical Garden constitutes a large percentage of the entire group of escaped plants in the urban flora of Kyiv, but was lower than expected. Probably this is due to rigid methodological criteria and peculiarities of introduction and cultivation of plants in the Botanical Garden. It has been established that only about 3.1 % of cultivated plants in Botanical Garden went beyond the boundaries of culture. In general, a group of escaped plants combines invasive plants that are threatening indigenous ecosystems, but also species that need protection.